2016
DOI: 10.3390/ph9040071
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin as a Modulator of P-Glycoprotein in Cancer: Challenges and Perspectives

Abstract: Multidrug resistance (MDR) presents a serious challenge to the efficiency of cancer treatment, and may be associated with the overexpression of drug efflux pumps. P-glycoprotein (P-gp) is a drug efflux pump often found overexpressed in cases of acquired MDR. Nevertheless, there are no P-gp inhibitors being used in the current clinical practice, due to toxicity problems, drug interactions, or pharmacokinetic issues. Therefore, it is important to identify novel inhibitors of P-gp activity or expression. Curcumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(44 citation statements)
references
References 59 publications
0
44
0
Order By: Relevance
“…Tumours become resistant to a great number of different drugs without structural or functional similarities, including anthracyclines, taxanes and Vinca alkaloids, and this hampers cancer treatments (An et al, ). Much of such resistance to cancer chemotherapy involves the multidrug resistance protein 1 (MDR1), an efflux pump that belongs to the family of ATP‐binding cassette transporters (ABC) (Lopes‐Rodrigues et al, ) and other proteins of the ABC superfamily such as the breast cancer resistance protein (ABCP or ABCG2) (Chen et al, ). Several studies have reported the involvement of the ECS in the mediation of resistance to anticancer drugs.…”
Section: Ecs and Drug Resistancementioning
confidence: 99%
“…Tumours become resistant to a great number of different drugs without structural or functional similarities, including anthracyclines, taxanes and Vinca alkaloids, and this hampers cancer treatments (An et al, ). Much of such resistance to cancer chemotherapy involves the multidrug resistance protein 1 (MDR1), an efflux pump that belongs to the family of ATP‐binding cassette transporters (ABC) (Lopes‐Rodrigues et al, ) and other proteins of the ABC superfamily such as the breast cancer resistance protein (ABCP or ABCG2) (Chen et al, ). Several studies have reported the involvement of the ECS in the mediation of resistance to anticancer drugs.…”
Section: Ecs and Drug Resistancementioning
confidence: 99%
“…Several anticancer agents derived from medicinal plants fail for treatment because it is the substrate of P-glycoprotein and the situation becomes worse if the compound can induce mdr-1 gene expression (Barthomeuf et al, 2005;Lopes-Rodrigues et al, 2016). Results of the study showed that even CL-6 and Caco-2 have different EPMC sensitivity, but it does not effect on mdr-1 expression in both cell lines.…”
Section: Discussionmentioning
confidence: 95%
“…ototoxicity, nephrotoxicity and neurotoxicity) (57). Curcumin might be a safe and effective inhibitor of P-glycoprotein (P-gp) to overcome multidrug resistance (MDR) in human cancer (58). In addition, some research has revealed that curcumin can sensitize tumors to different chemotherapeutic agents including doxorubicin, 5-FU, paclitaxel, vincristine, oxaliplatin, etoposide and so on in numerous cancers (e.g., breast,colon, pancreas, gastric, liver, blood, lung, prostate, and ovary) (59).…”
Section: Some Single Tcms With Properties Of Promoting Blood Circulatmentioning
confidence: 99%